Honja sanŭn saramdŭl = Aloners [videorecording (DVD)] - Hong, Sŏng-ŭn, 1988-; Hong, Sŏng-ŭn, 1988-; Gong, Seung-yeon; Chŏng, Ta-ŭn, 2001- (Film Movement series., 2023)
Jina is the top employee at a call center, but despite talking to customers all day, she has shut out the world beyond her headset; she lives alone, eats alone, sleeps alone, and her cell phone is her constant companion. When one day she's tasked with training a friendly and nav̐e new hire, her icy armor is threatened. At the same time, she must navigate an incessantly ingratiating new neighbor, and an increasingly urgent phone call from her father, leaving Jina teetering on the edge of an existential crisis, forcing he to confront why she has isolated herself all these years.